'¿Está mal olvidar?' Psychological Suffering in Jorge Accame's Cuatro poetas Tetralogy. Issue 10 (26th November 2017) - Macintyre, Iona
Abstract: Argentinian writer Jorge Accame's tetralogy of narratives published between 2000 and 2010 are spin-offs from his 1999 fictional anthology of poetry Cuatro poetas, in which he concocted the work of four writers. What appears superficially to be a playful and imaginative literary project in fact contains an exploration of some very painful topics rooted in the recent history of Argentina. These include the dictatorship as well as present-day social problems. This article considers the Cuatro poetas series as an exploration of the generation of writers that grew up during the dictatorship. Rather than using trauma theory's notion of 'unspeakable' as the guiding concept, this article examines attempts to express inner pain by these imagined writers, whose very profession calls for the articulation of experience using words.